COVID-19 Diagnosis and Treatment Challenges in Rural India - Chandra S.; Kanojiya S.; Verma A.R.; Kumar Y. (My University, 2025)
COVID-19 was first identified in Wuhan, China in December 2019. India is the second most affected country of the world. About 516 million people have been affected worldwide by it so far, and approximately 6 million deaths have been caused. In India, more than 40 million people have been infected according to official data released by the government. Early detection of COVID-19 infection is the first part to deal with this pandemic. However, detection of COVID-19 infection is the biggest problem in rural India because of bad connectivity and poor medical facilities. After a certain period of time there are waves of increasing numbers of cases because of its variants. Rural India faced the problem of shortage of medical resources because of a spike in the number of cases in a region. The goal of this study is to develop a deep learning model that can help in detecting COVID-19 cases using chest x-rays, thus leading to inexpensive and fast early detection of COVID-19 to prevent its spread. © 2023, IGI Global.